Increasing Growth and Production of Green beans (Vigna radiata L.) by Providing Organic Fertilizers with Goat Manure and Variations in Planting Spacing - Zamriyetti Zamriyetti; Sri Mahareni Br Sitepu; Rosmaria Girsang; Khairul Romadan Surbakti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Green bean is a food ingredient that is extensively consumed by the general public and is categorized as having a high frequency of use. This study seeks to determine the effect of organic goat manure on the growth and yield of green beans (Vigna radiata L). It will also examine the impact of plant spacing and the interaction between the two factors. This investigation utilized a factorial randomized block design (RBD) with two regimens and three replications. The first variable was the amount of goat manure organic fertilizer applied to each plot: 0 kg/plot, 2 kg/plot, 4 kg/plot, and 6 kg/plot. The second factor is the variation of the different spacing sizes, which are 20 x 40 cm, 25 x 40 cm, 30 x 40 cm, and 35 x 40 cm. In this study, the following parameters were observed: plant height, number of productive branches, number of pods per sample, number of pods per plot, pod production per sample, pod production per plot, and 100 seed weight per sample. The study's results indicated that the application of goat manure organic fertilizer, the assessment of different plant spacings, and the interaction between the two treatments had no significant effect on any of the parameters. Include plant height, number of productive branches, number of pods per sample, number of pods per plot, pod production per sample, pod production per plot, and 100 seed weight per sample.